Richard Linklater - Johnson, David T., 1972- (Book collections on Project MUSE., 2012)
Richard Linklater's filmmaking choices seem to defy basic patterns of authorship. From his debut with the inventive independent narrative Slacker, the Austin-based director's divergent films have included the sci-fi noir A Scanner Darkly, the socially conscious Fast Food Nation, the kid-friendly The School of Rock, the nostalgia-soaked Dazed and Confused, and the twin romances Before Sunrise and Before Sunset. Yet throughout his varied career spanning two decades, Linklater has maintained a sense of integrity while working within a broad range of budgets, genres, and subject matters._x000B_Identifying a critical commonality among so much variation, David T. Johnson analyzes Linklater's preoccupation with the concept of time in many of his films, focusing on its many forms and aspects. Crucially filling a gap in critical studies of this American director, the volume concludes with an interview with Linklater discussing his career.